2019
DOI: 10.22159/ajpcr.2019.v12i3.30299
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Hepatoprotective Effects of Virgin Coconut Oil at Maximum Physical Activity

Abstract: Objective: The purpose of this study was to determine the protective effects of virgin coconut oil (VCO) treatment on hepatic oxidative stress and antioxidant defenses after maximum physical activity. Methods: This study used 24 healthy male rats. The rats were divided into four groups randomly consisted of six rats in each group. The control group (P0) was given 2 mL water, the treatment groups (VCO-1, VCO-2, and VCO-4) were given VCO 1 ml/200 g BW, 2 ml/200 g BW, and 4 ml/200 g BW, respectively, per da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The outcome demonstrates that the coconut oil groups' (CO-1, CO-2, and VCO-4) liver GPx levels were substantially greater than those of the C group's (p 0.05), with increased rates of, respectively, 57.68, 96.33, and 169.62%. 150 Malondialdehyde (MDA) levels in the liver were significantly lower in fish receiving meals containing CO; the lowest levels were observed in fish getting food containing 50% coconut oil (P 0.05; 57.68, 96.33, and 169.62%, respectively). 151 A decrease in the optical density (OD) at 240 nm for 1 min next to the breakdown of H 2 O 2 was used to assess the catalase activity.…”
Section: Autoxidation Of Oils Natural Oils Have Long Been Valuedmentioning
confidence: 99%
“…The outcome demonstrates that the coconut oil groups' (CO-1, CO-2, and VCO-4) liver GPx levels were substantially greater than those of the C group's (p 0.05), with increased rates of, respectively, 57.68, 96.33, and 169.62%. 150 Malondialdehyde (MDA) levels in the liver were significantly lower in fish receiving meals containing CO; the lowest levels were observed in fish getting food containing 50% coconut oil (P 0.05; 57.68, 96.33, and 169.62%, respectively). 151 A decrease in the optical density (OD) at 240 nm for 1 min next to the breakdown of H 2 O 2 was used to assess the catalase activity.…”
Section: Autoxidation Of Oils Natural Oils Have Long Been Valuedmentioning
confidence: 99%
“…Therefore, the supplementation of exogenous antioxidant from diet becomes important to protect cells against the deleterious effect of ROS [16]. The results of several studies reported that the administration of antioxidants derived from natural or synthetic products from outside the body is required to neutralize the free radicals formed during physical activity, especially strenuous physical activity [17], [18], [19, [20].…”
Section: Introductionmentioning
confidence: 99%